MYCOLOGICAL STUDY OF RECURRENT APHTHOUS STOMATITIS IN SAMARRAH CITY - Azawi, Gaafar Jameel Ibrahim; Farhan, Rafal Khaleel (International Journal of Psychosocial Rehabilitation, 2020)
RAS is some of the best communal mucosal conditions of the oral cavity. The etiopathogenesis of RAS is uncertain, but influencing factors include stress, trauma, food allergy, and genetic factors. Stress and microorganisms have a role in the onset and recurrence of RAS.This study aim at clarifying the association between fungus and aphthous ulcer and detection of virulence factors .The current work represented an observational cross- sectional study which was conducted during the period extending from the first of July 2019 to the end of November 2019, with 4-5 regular working hours. The total number of patients in this study was 150 patients attending to the ENT out-patients in Sammarra General Hospital.The total number of patients with recurrent aphthous stomatitis in our study was 150 patients attending to the ENT out – patients in Sammarra General Hospital during the period between 1st of July to end of November 2019. All of these patients have recurrent aphthous stomatitis, 68 (45.33%) were male patients and 82(54.66%) were female patients, while, higher prevalence in age 21-40years 59(39.3%).In our study, the results were that fungal infection as a cause of aphthous stomatitis is infrequent, but in some cases there may be super-added fungal infection in addition to presence aphthous ulceration .